Acute pancreatitis: Early Management - Kibria, Md Golam (Bangladesh Journal of Medicine, 2023)
Abdominal pain caused by acute pancreatitis (AP) is not uncommon in day to day medical practice worldwide. AP is the sudden inflammation of the pancreas, and it may be confined to the pancreas, or may be more life-threatening, affecting all organs and systems. It progresses mildly in 80% of patients and resolves with treatment, but in cases of severe AP, with mortality of around 30% has been recorded. AP is most often established by clinical symptoms and at least threefold raised enzymes and by imaging (any two of these three).In the management AP, treatment is mainly related to the severity of the disease and approaches are constantly being updated. With early diagnosis and treatment, most of the patients can be discharged, and the development of complications and mortality can be reduced. Hemodynamic status should be assessed immediately upon presentation and resuscitative measures begun as needed. Early targeted fluid therapy within the first 48 h is critical to improve the outcome of severe AP. Patients with organ failure and or SIRS should be admitted to an ICU /HDU whenever possible. Emergency management decision are early fluid management strategy, utility and timing of antibiotics, the timing and type of nutritional support and in relevant cases endoscopic retrograde cholangiopancreatography (ERCP) and cholecystectomy approachescan change the course of the disease and the length of stay in the hospital. Therefore, emergency management is important.Enteral nutrition is recommended to prevent infectious complications, whereas parenteral nutrition should be avoided.Routine use of prophylactic antibiotics in patients with severe AP and or sterile necrosis is not recommended.In patients with infected necrosis, antibiotics known to penetrate pancreatic necrosis may be useful in delaying intervention, thus decreasing morbidity and mortality. Successful clinical management requires close interdisciplinary cooperation and coordination from experienced gastroenterologists, intensive care physicians, surgeons, and radiologists. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 188-189